ANALISIS RETRIBUSI JASA UMUM, RETRIBUSI JASA USAHA DAN RETRIBUSI PERIZINAN TERTENTU TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN BANGKA - Desy Yunita; Nana Adriana (JEM Jurnal Ekonomi dan Manajemen, 2020)
This study aims to determine the effect of acceptance of public service levies, business service fees, and certain licensing fees on Bangka Regency's Original Revenue. The data analysis method used is the Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test), Multiple Linear Regression Analysis, Coefficient of Determination (R2), and Hypothesis Testing (Simultaneous Test (F Test), Partial Test (t-Test) The process uses SPSS The results of this study indicate that data analysis using the Multiple Linear Regression analysis methods shows that Public Service Charges, Business Service Charges, and Certain Licensing Fees have a significant effect on Regional Original Income (PAD) in Bangka Regency. Further research is recommended to add variables or conduct research in other governments and using different methods